2008
DOI: 10.1057/jit.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

IS Integration and Business Performance: The Mediation Effect of Organizational Absorptive Capacity in SMEs

Abstract: A fundamental result of the information technology (IT) and business performance literature is that IT is not a driver of performance per se. However, it can be associated with higher performance if accompanied by organizational change. The identification of the variables describing organizational change is still on-going work. This paper focuses on organizational absorptive capacity and analyses its effects on the relationship between IT and business performance in small and medium enterprises (SMEs). Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 87 publications
5
79
0
3
Order By: Relevance
“…Our conceptual model draws heavily on the strategy literature and the strategic necessity hypothesis in asserting that although IT is a necessary factor, it rarely, in-and-of-itself, generates sustainable performance advantages (Clemons and Row 1991). In other words, the business value that is generated by IT is dependent upon the combination of complementary technical, organizational and human resources (Francalanci and Morabito 2008). Figure 1 illustrates the proposed combination of lower-and meta-capabilities to explain hierarchically how CRM contributes to firm performance.…”
Section: Conceptual Model Of Crm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Our conceptual model draws heavily on the strategy literature and the strategic necessity hypothesis in asserting that although IT is a necessary factor, it rarely, in-and-of-itself, generates sustainable performance advantages (Clemons and Row 1991). In other words, the business value that is generated by IT is dependent upon the combination of complementary technical, organizational and human resources (Francalanci and Morabito 2008). Figure 1 illustrates the proposed combination of lower-and meta-capabilities to explain hierarchically how CRM contributes to firm performance.…”
Section: Conceptual Model Of Crm Performancementioning
confidence: 99%
“…For example, Francalanci and Morabito (2008) identify that the link between information systems and firm performance is mediated by the absorptive capacity of the firm. Brynjolfsson and Hitt (1996) argue that the business value from IT is only generated when the IT is absorbed within the firm, as a routinized element of a company's value chain.…”
Section: It Infrastructurementioning
confidence: 99%
“…138 SMEs in Malaysia Inter-organizational relationships were affecting Malaysian SMEs' decision to adopt e-business in the supply chain The findings of both the contingency and configuration approach indicated that supply chain integration was related to both operational and business performance Söderberg and Bengtsson (2010) 15 SMEs in Sweden The results indicate that there is a strong relationship between SCM maturity and SC performance in SMEs and some relationships between SCM maturity and financial performance Tumaini and Zheng (2011) 229 SMEs in Tanzanian The study found that SMEs still face obstacles like knowledge, financial resources and technology IT integration is an important need for SMEs because IT integration will produce precise information that can improve firm efficiency, customer satisfaction, and firm productivity (Volkoff, Strong & Elmes, 2005;Berente, Vandenbosch & Aubert, 2009;Sampaio, Saraiva & Domingues, 2012;Francalanci & Morabito, 2008;Yen-Teoh & Pan, 2009;Simon & Petnji-Yaya, 2012). Thus, the more integrated the information system, the better the firm performance.…”
Section: Samples/countries Findingmentioning
confidence: 95%
“…This is supported by the study by Wolff and Pett (2006), who asserted that firms that innovate tend to have greater returns on investment. Moreover, according to their study of 466 SMEs in Italy, Francalanci and Morabito (2008) proposed that the integration of information systems might mediate firm absorptive capacity.…”
Section: Mediating Effect Of Service Innovation On the Relationship Bmentioning
confidence: 99%